CAMBODIA & ANGKOR - Chavanat, Damien, author 644833; Herberstein, Elsie, author 644835; Smith, Justin Creedy, photographer 644836; Davidson, Lisa, translator 644837 (Singapore : Archipelago Press, 2007)
The "Trois Moustiquaires", winners of the Lonely Planet 2001 award for their book Zanzibar, Carnets de voyage, have turned their unique gaze upon Cambodia. They were guided by a fourth "Moustiquaire", Benito, founder of the leading Cambodian humanitarian organisation for children. With sketches, words, photographs and illustrations Elsie, Justin and Damien have captured a land and its people, the heirs to one of Southeast Asia's most fascinating civilisations, blighted by human tragedy in recent history. Travelling throughout the country; from the Gulf of Siam to the red hills of Ratanakiri; the streets of Phnom Penh to the rice paddies of Lake Tonle Sap, the banks of the Mekong to the mysterious temples of Angkor, lost for centuries deep in the forest, they have distilled the essence of Cambodia today.